ANALISIS MANAJEMEN RANTAI PASOKAN BERAS PERUM BULOG SUBDIVRE III SURAKARTA - Ega Febryani; Yohanes Djoko Suseno; Erni Widajanti (Universitas Slamet Riyadi, 2020)
Perum Bulog Subdivre III Surakarta is a company that produces products in the form of rice. The purpose of this study is to determine the performance of supply chain management that is currently running in Perum Bulog Subdivre Surakarta whether it is optimal or not for the company. This research is a case study. The type of data in this study uses qualitative data and quantitative data. Sources of data obtained from primary and secondary data. This research uses interview, observation, and literature study as well as documentation in collecting data. Management of Supply Chain Management at Perum Bulog Subdivre III Surakarta involving farmers / partners, Perum Bulog Subdivre III Surakarta and consumers are running optimally. The supply chain that has been run already has clear objectives and chain members who carry out their duties are also in accordance with their role. Policy alternatives that can be used to assist in optimizing supply chain performance include trust building, government support, additional technological resources, and contractual agreements between farmers / partners with Perum Bulog Subdivre III Surakarta and between Perum Bulog Subdivre III Surakarta and consumers.